The Pengaruh Modifikasi Buah dan Sayur Terhadap Konsumsi Buah dan Sayur Pada Anak Sekolah Dasar Pangkalan Kerinci - Nurwahidah Nurwahidah; Tri Krianto Karjoso; Yesica Devis; Meriwati Mahyuddin; Mitra Mitra (Jurnal Kesehatan Komunitas, 2023)
Efforts to increase fruit and vegetable consumption in school-age children are carried out by providing training to parents and providing video tutorials on fruit and vegetable modification on social media (WA Group) through the intermediary of teachers. The low coverage of Clean and Healthy Lifestyle Behavior (PHBS) on fruit and vegetable consumption indicators in Pelalawan Regency and the results of the initial survey which showed the low frequency of bringing fruit and vegetable supplies to school children were the reasons behind this research. This study aims to determine the effect of the amount of fruit and vegetable consumption in elementary school children in Pangkalan Kerinci. This study uses a quasi-experimental research design with pre test-post test non-equivalent control group design. The study was conducted in July – August 2022 with a sample of 100 students (50 in the treatment group and 50 in the control group). Data analysis was carried out univariate and bivariate using the Wilcoxon test and 1 sample T-test. The results found the highest significant average of fruit and vegetable consumption after the intervention was 63.1 grams and 134.1 grams in the treatment group and 63.9 grams and 128.8 grams in the control group. The conclusion of this study shows that there is a difference between the frequency of consumption of fruits and vegetables before and after the intervention. Suggestions in this study is that it is recommended for schools to make an appeal letter related to the fruit and vegetable consumption program once a week and expected to the Health office for increasing teachers education related to fruit and vegetable consumption in primary school children. Keywords : Fruits and Vegetabels, Elementary School, Modification.